2012
DOI: 10.1177/0018720812442087
|View full text |Cite
|
Sign up to set email alerts
|

Highly Automated Driving, Secondary Task Performance, and Driver State

Abstract: Précis: This study examined the effect of changes in workload on performance in highly automated and manual driving. Variations in workload were also observed using blink measures. Results showed good driver response to incidents in the highly automated condition and some predictions in workload levels by blink frequency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
150
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 335 publications
(170 citation statements)
references
References 23 publications
7
150
1
1
Order By: Relevance
“…Safety has become increasingly pervasive, to the point where driver autonomy is potentially eroded by safety technologies of increasingly intrusive form (Merat et al, 2012). As the burdens of control are reduced for the driver, so it becomes increasingly possible for d i e s to be engaged in other tasksultimately of course expressed in the form of autonomous vehicles of the type being developed by Google (Markoff, 2010).…”
Section: Safetymentioning
confidence: 99%
“…Safety has become increasingly pervasive, to the point where driver autonomy is potentially eroded by safety technologies of increasingly intrusive form (Merat et al, 2012). As the burdens of control are reduced for the driver, so it becomes increasingly possible for d i e s to be engaged in other tasksultimately of course expressed in the form of autonomous vehicles of the type being developed by Google (Markoff, 2010).…”
Section: Safetymentioning
confidence: 99%
“…Martens et al [17] achieved the same result for car drivers in control of semi-and highly automated driving. Merat et al [19] found an interaction effect between automation and workload through a non-visual secondary task in which manual and highly automated driving were affected more than was semi-automated driving.…”
Section: Introductionmentioning
confidence: 99%
“…A more differentiated picture of these contradictory results is provided by recent studies on the consequences of highly automated driving. In a simulation study, Merat et al [42] examined the effects of performing a secondary task on driving behavior during automated driving. The study showed that reactions to critical incidents in highly automated and manual driving conditions without a secondary task were comparable.…”
Section: Automation In the Carmentioning
confidence: 99%